Antifungal effect of electrospun nanofibers containing cetylpyridinium chloride against Candida albicans - Valdirene Alves dos SANTOS; Patricia Verônica Aulestia VIERA; Adriano Marim de OLIVEIRA; Maria Helena Ambrosio ZANIN; Maria Aparecida BORSATTI (Sociedade Brasileira de Pesquisa Odontológica, 2014)
It is known that cetylpyridinium chloride (CPC) has in vitro and in vivo antifungal action against Candida albicans, with advantages over other common antiseptics. A CPC delivery-controlled system, transported in polymer nanofibers (PVP/PMMA), was developed to increase the bioavailability of the drug in contact with the oral mucosa. The objectives of this study were to determine if CPC in nanofiber has antifungal action against C. albicans, and in what concentration it must be incorporated, so that the fraction released can yield an inhibitory concentration. The nanofiber was prepared by electrospinning, and sterilized with gamma irradiation. Nanofiber disks with 0.05%, 1.25%, 2.5% and 5% CPC, with 5% miconazole (MCZ) and with no drug, as well as filter paper disks with 5% CPC, with 5% MCZ and with no drug were used in this study. A Candida albicans suspension (ATCC 90028) was inoculated in Mueller-Hinton Agar plates. The disks were placed on the plates and the inhibition zone diameters were measured 48h later. The nanopolymeric disks contracted in contact with the agar. All the concentrations of CPC incorporated in the nanofiber presented inhibitory action against C. albicans. Concentrations of 2.5% and 5% CPC presented a significant advantage over the nanofiber with no drug, proving the antifungal action of CPC. Under these experimental conditions, 5% CPC has greater inhibitory action against C. albicans than 5% MCZ, both in nanofiber and in filter paper. A modification made in the polymer to decrease the contraction rate may allow a larger inhibition zone to be maintained, thereby increasing the clinical usefulness of the polymer.